Estimation of the optimal time needed for weaning of Intensive Care Unit tracheostomized patients on mechanical ventilation. A prospective observational study. - Marinaki, Chrisoula; Kapadochos, Theodoros; Katsoulas, Theodoros; Rubbi, Ivan; Liveri, Athanasia; Stavropoulou, Areti; Bonacaro, Antonio; Papageorgiou, Dimitrios (Acta Biomedica Atenei Parmensis, 2023)
Background and aim: Determining the time that is required for weaning, as well as the factors that influence it can be used for the appropriate planning of patient’s medical and nursing care. The aim of this study is to estimate the optimal time an Intensive Care Unit (ICU) patient with tracheostomy needs to wean from mechanical ventilation. Methods: This prospective observational study was conducted on 162 patients from two general hospitals in Athens, Greece. A specially designed recording form was created to conduct the study. The Statistical Package for the Social Sciences (SPSS) v.25 for Windows was used to record and analyze the data. The level of statistical significance was set at α=5%. Results: Results were found after comparing and associating the demographic and clinical characteristics and medical history of patients with the duration of weaning, the length of post-tracheostomy ICU stay and the time from intubation to tracheostomy. Conclusions: According to the results of our study, there are various factors that affect success and duration of weaning. More specifically, there seems to be an association between duration of weaning and age, number of closure attempts, success of closure, time from intubation to tracheostomy, length of the patient’s post-tracheostomy ICU stay and diagnosis upon admission. The shorter the duration of weaning, the greater the benefits for the patients themselves, such us avoiding respiratory damage, reduction of mortality and morbidity and preventing of length of patient’s ICU stay.